Qualidade de vida de atletas de elite do estado de Goiás - Pereira, Ernesto Flávio Batista Borges (Universidade Federal do Tocantins, 2019)
Quality of Life (QL) is understood as a subjective construct linked to the individual satisfaction in different spheres of his/her life. The improvement in their sporting environment may have a reflection on their social context, as well as on the level of athletic performance. The goal of this research was to evaluate the elite athletes’ QL from Goiás State. To investigate it, an exploratory descriptive method with quantitative analysis was used. The sample was composed of 20 (twenty) street athletes from the state of Goiás, 10 (ten) males and 10 (ten) females. A semi-structured questionnaire was used with specific closed questions. Data analysis was performed through the Statistical Package for Social Sciences - SPSS 16.0, presenting the median. The main results showed that male athletes presented ages ranging from 18 to 44 years (average of 32.3 years) and female athletes between 18 and 52 years (average of 33.7 years). Of the 20 athletes interviewed, 65% work and 35% do not.They only train. As for marital status, 45% of the individuals were married; 45% singles and 10% divorced / separated. Regarding the best personal mark obtained in the course of 10km, in malesit was obtained from 2003 on with results varying between 28'56 "and 31'45" (30'40"± 0"87), and the best mark current ranged between 30'02" and 35'04" (31'39"±1'62"). In female, the best personal mark was obtained during the last 10 years with results varying between 33'00" and 43'30" (37'39"± 3'18") and the best current mark ranged between 30'00" and 46'06" (40'01"±4'07"). In the descriptive and comparative analysis of the WHOQOL-bref by domain, the psychological score was the highest (73.33 ± 10.68) while the environmental was the lowest one (60.78 ± 15.09). Regarding the Quality of Life Questionnaire for Athletes - QQVA, the descriptive and comparative analysis by size showed that the biological scorewas the highest (64.38±21.18) while the psychological was the lowest one (53,75±24.70). These results demonstrate that athletes, in a training and competition environment, are qualitatively satisfied in the social-environmental dimension, which covers aspects such as basic health conditions, interpersonal relationships in the sports environment and, in relation to aspects of planning and periodization of the sports training, in the context of their athletic QL.